Extensive Bone Marrow Necrosis: Initial Presentation in Sickle Cell Anemia—A Case Report and Review of the Literature - Sameera A. Alsafwani; Abdulwahed Al-Saeed; Rehab Bukhamsin (Case Reports in Hematology)
Bone marrow necrosis (BMN) is a rare clinical entity that was first described in an autopsy of a sickle cell disease (SCD) patient and is defined as ill-defined necrotic cells in an amorphous eosinophilic background with preservation of cortical bone. The pathophysiology of BMN is not well known; however, occlusion of the bone marrow microcirculation with subsequent hypoxia and cell injury has been thought to be common underlying features. Malignancy has been identified to be the primary cause in 90% of the cases whereas SCD was found in only 2%. In this report we present an unusual case of SCD with late onset of the disease whose initial presentation was extensive BMN. The patient was not known previously to have SCD, when suddenly she presented with severe cytopenias and marked elevation in serum lactate dehydrogenase (LDH). Bone marrow examination was done to exclude bone marrow infiltration, and BMN with dilated marrow sinuses full of irreversibly sickled cells were the unexpected findings. Patients with a mild SCD phenotype are at high risk of BMN. Thus, a high index of suspicion must be borne in mind, particularly in an area of high SCD prevalence, to recognize and prevent this catastrophic complication.